ILP Models for the single PON Access Network Design Problem - Lopes, M. J.; L. Gouveia; Sousa, A. (EURO - INFORMS MMXIII - 26th European Conference on Operational Research, 2013)
A PON is an optical access network connecting a Central Office to a set of terminals using optical fibres and splitters, installed on intermediate nodes. For each PON we have to define where to install splitters and how to connect all elements through fibres. There are costs associated with intermediate nodes, splitter types and fibre connections. We consider a single PON and define the minimum cost design problem in the context of densely populated urban areas, proposing different discretized formulations and valid inequalities for this problem. Keywords: Passive Optical Networks, Network Optimization, ILP Models, Telecommunications